ØªØ·Ø¨ÙŠÙ‚ Ø¥Ø¯Ø§Ø±Ø© Ø§Ù„Ø¨Ø±Ù†Ø§Ù…Ø¬ Ø§Ù„Ù…ÙƒØ«Ù Ø§Ù„Ø¹Ø±Ø¨ÙŠ ÙÙŠ Ø¬Ø§Ù…Ø¹Ø© ØªÙˆÙ„ÙˆÙ†Ø¬ Ø£ØºÙˆÙ†Ø¬ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© - Nurcholis, Ahmad (Jurnal Pendidikan Islam, 2016)
This study contradicts the fact that nowadays many educational institutions conducting an intensive program that is effective for improving the quality of learning Arabic. The goal is to prepare students to have the ability to compete in the face of competition in the future. Therefore, STAIN Tulung manage intensive Arabic program with a clear vision and mission, strategically where, the participation of all elements of the school to make the maximum contribution to the strengthening of institutions. The problem is a graduate of the institution have not reached a satisfactory quality, are still required to efforts to improve the quality of learning Arabic. The method used in this research is grounded research. Data collection techniques used were observation, interviews and documentation. The results showed that penyenggaraan intensive Arabic program at STAIN Tulung remains effective for several reasons, in ataranya there is no compatibility between the various elements in the institutions and the lack of continuity between the material being taught with the use of language in learning. Â